The practice of exclusive breastfeeding: its socio-demographic determinants in Kashmir, North India - Naik, Suhail A.; Irshad, Mohd.; Rasool, Ghulam; Rafiq, Wasim A. (International Journal of Contemporary Pediatrics, 2019)
Background: Breastfeeding is a well-established and recommended intervention for the improvement of child nutrition. Formula feeding is a major public health problem. Objective of the current study was to know the significance of demography, socioeconomic, parental education and employment and mode of delivery on exclusive breast-feeding Kashmir, North India. Methods: A prospective hospital-based study, carried out in the Department of Pediatrics, G.B Pant Hospital Srinagar Kashmir India over the period from 2014 July to June 2015. A teaching, research and tertiary care hospital at Srinagar Kashmir North India. All the mothers who were having infants in the age group 0 to 6 months were included in study. Procedure of this variables recorded were modes of feeding, demographics, socioeconomic status, literacy level, mode of delivery, place of delivery etc. Results: A total of 600 mothers were included in study. Less than 35% of mothers were exclusively breast feeding their infants. Exclusive breast feeding was significantly high in babies born by normal vaginal delivery, more than 3 antenatal visits, mother knowing advantages of breast feeding and higher parental education. Conclusions: Exclusive breast feeding is very low (less than 35%) in this part of world and formula feeding is a major public health problem.